Economic impact and risk analysis of integrating sustainable aviation fuels into refineries - Carlson, Nicholas A.; Talmadge, Michael S.; Singh, Avantika; Tao, Ling; Davis, Ryan (Frontiers in Energy Research, 2023)
The growth of the aviation industry coupled with its dependence on energy-dense, liquid fuels has brought sustainable aviation fuel (SAF) research to the forefront of the biofuels community. Petroleum refineries will need to decide how to satisfy the projected increase in jet fuel demand with either capital investments to debottleneck current operations or by integrating bio-blendstocks. This work seeks to compare jet production strategies on a risk-adjusted, economic performance basis using Monte-Carlo simulation and refinery optimization models. Additionally, incentive structures aiming to de-risk initial SAF production from the refiner’s perspective are explored.